Synthesis, characterization and antimicrobial activity of novel benzofuran- and thiophene-containing diketoxime derivatives - Coskun, Demet; Gur, Seher; Coskun, Mehmet Fatih (Serbian Chemical Soc, 2017)
The aim of this study was the preparation of 1,1'-(2,5-thiophenediyl)bis[1-(2-benzofuranyl)methanone] (2), the corresponding diketoxime (3), and the ether and ester derivatives (4a-e) of the diketoxime. These compounds were prepared in good yields. Minimum inhibitory concentrations (MIC) of the synthesized compounds 1-4 were determined against Salmonella enterica subsp. enterica serovar Typhimurium, Escherichia coli and Staphylococcus aureus. Among the synthesized compounds, 1 and 4e showed good activity against E. coli, S. enterica and S. aureus.
Keywords: bisbenzofuran; thiophene; diketoxime; antimicrobial activity